Protest kitchen : fight injustice, save the planet, and fuel your resistance one meal at a time - Adams, Carol J.; Messina, Virginia (Conari Press, an imprint of Red Wheel/Weiser, LLC, 2018)
"Protest Kitchen is an empowering guide to the food and lifestyle choices anyone can make for positive change in the face of the profound challenges of our time. Our food choices have much more of an impact than most people imagine. They not only affect our personal health and the environment, but are also tied to issues of justice, misogyny, national security, and human rights. Protest Kitchen is the first book to explore the ways in which a more plant-based diet challenges regressive politics and fuels the resistance. A provocative and practical resource for hope and healing, Protest Kitchen, features over 50 vegan recipes (with alternatives for "aspiring vegans") along with practical daily actions such as: Substitute cow's milk in your coffee and cereal for any of a variety of delicious non-dairy milks. This will help lower the release of methane gas that contributes to global warming Use a smartphone app when buying chocolate to avoid supporting African farmers who use child-labor, even child slavery, to supply cacao beans to the food industry Make your own cleaning supplies and wood polish; it's frugal and avoids reliance on products that may be tested on animals"--